FORMATION AND OPTIMIZATION OF BUSINESS PROCESS MANAGEMENT AT MANUFACTURING ENTERPRISES - CHOBITOK, Viktoriia; PROTSENKO, Valentina; HNATCHENKO, Yehor (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article addresses the issue of optimization of business processes in manufacturing enterprises, highlighting its growing relevance in the context of rapid economic changes and intensified competition. At the current stage of economic development, enterprises face dynamic transformations in technology, consumer demand, and competitive environments, which necessitate the constant search for effective managerial solutions. The research stresses that optimization of business processes is not limited to solving isolated operational problems but involves the development of systematic approaches and methodologies applicable across different stages of the production cycle. The study emphasizes that the manufacturing sector, as one of the key drivers of national economies, encounters unique challenges related to market dynamics, technological innovations, and consumer preferences. Theoretical and practical significance of the research lies in substantiating models and methods of business process optimization that enhance efficiency, adaptability, and competitiveness of enterprises. The article reviews contributions of domestic and foreign scholars in the field of process management and underlines the need for further investigations due to continuous shifts in market conditions and decision-making requirements. Business process optimization is presented as a strategic instrument that ensures sustainability and competitiveness of enterprises. The article distinguishes between core processes (production), supporting processes (logistics, maintenance), managerial processes (planning, control), and development processes (innovation, technology improvement), showing their interdependence and critical role in value creation. The research proposes principles of process optimization, such as compression of stages, reduction of unnecessary approvals, and transition to more effective environments, which allow enterprises to minimize time and resource losses while maintaining flexibility and quality. The methodological framework includes a six-stage evaluation process: system diagnostics, analysis of quantitative and qualitative indicators, identification of bottlenecks, assessment of improvement potential, modeling, and implementation of changes. Modeling, as noted, plays a vital role in formalizing and visualizing processes, making them easier to analyze, optimize, and integrate into management systems. Unlike radical reengineering, optimization is presented as a flexible and incremental approach, suitable for large-scale production enterprises where gradual improvements may deliver more stable and sustainable results. A combined use of reengineering for fundamental redesign and optimization for continuous refinement is recommended as the most effective approach to long-term competitiveness. The research concludes that optimization of business processes helps identify and eliminate inefficiencies such as duplication of functions, bottlenecks, excessive costs, and poor coordination. Business processes in manufacturing enterprises are described as complex and dynamic systems that require high levels of organization and adaptability. The study emphasizes that the introduction of modern optimization methods not only contributes to operational efficiency but also creates a foundation for sustainable development and resilience in the face of market turbulence. Overall, the results of the research provide a valuable contribution to the theory and practice of enterprise management, offering models and recommendations that may enhance the competitiveness and sustainability of manufacturing enterprises. The proposed methodological approaches may serve as an effective guide for managers in adapting business processes to the challenges of the modern economic environment, thereby ensuring the long-term growth and stability of enterprises in the manufacturing industry.